Expression of voltage-gated Ca2+ channels, Insp3Rs, and RyRs in the immature mouse ovary - Daniel Bahena-Alvarez; Diana Millan-Aldaco; Ruth Rincón-Heredia; Nancy Escamilla-Avila; Arturo Hernandez-Cruz (BMC, 2022)
Abstract Background The postnatal mammalian ovary undergoes a series of changes to ensure the maturation of sufficient follicles to support ovulation and fecundation over the reproductive life. It is well known that intracellular [Ca2+]i signals are necessary for ovulation, fertilization, and egg activation. However, we lack detailed knowledge of the molecular identity, cellular distribution, and functional role of Ca2+ channels expressed during folliculogenesis. In the neonatal period, ovarian maturation is controlled by protein growth factors released from the oocyte and granulosa cells. Conversely, during the early infantile period, maturation becomes gonadotropin-dependent and is controlled by granulosa and theca cells. The significance of intracellular Ca2+ signaling in folliculogenesis is supported by the observation that mice lacking the expression of Ca2+/calmodulin-dependent kinase IV in granulosa cells suffer abnormal follicular development and impaired fertility. Results Using immunofluorescence in frozen ovarian sections and confocal microscopy, we assessed the expression of high-voltage activated Ca2+ channel alpha subunits and InsP3 and ryanodine receptors in the postnatal period from 3 to 16 days. During the neonatal stage, oocytes from primordial and primary follicles show high expression of various Ca2+-selective channels, with granulosa and stroma cells expressing significantly less. These channels are likely involved in supporting Ca2+-dependent secretion of peptide growth factors. In contrast, during the early and late infantile periods, Ca2+ channel expression in the oocyte diminishes, increasing significantly in the granulosa and particularly in immature theca cells surrounding secondary follicles. Conclusions The developmental switch of Ca2+ channel expression from the oocytes to the perifollicular cells likely reflects the vanishing role of the oocytes once granulosa and theca cells take control of folliculogenesis in response to gonadotropins acting on their receptors.